VISTA is associated with immune infiltration and predicts favorable prognosis in TNBC - Zhang, Mi; Zhang, Juan; Liu, Na; Wang, Biyuan; Zhou, Yan; Yang, Jin (Frontiers in Oncology, 2022)
Background V-domain Ig-containing suppressor of T cell activation (VISTA), a critical immune checkpoint protein, can regulate the immune system. Nevertheless, little information is available on the expression level of VISTA and its clinical significance as well. The immunological and prognostic role of VISTA in triple-negative breast cancer (TNBC) still remains unclear. Methods The clinical significance and expression of VISTA in TNBC were examined using RNA sequencing and clinical data. Cancer single-cell state atlas (CancerSEA), gene set enrichment analyses (GSEA), single sample GSEA, ESTIMATE algorithm, immunohistochemistry (IHC) were utilized to assess the functions of VISTA. Results VISTA was down-regulated and closely associated with good prognosis in TNBC. The expression of VISTA was higher in Immunity-H group and immunomodulatory (IM) subtype. The level of VISTA expression in TNBC gradually increased with the degree of stromal tumor infiltrating lymphocytes (sTILs) infiltration. In addition, the high expression of VISTA was strongly linked to higher proportion of CD8 (+) T cell and M1 macrophages. Conclusion VISTA was remarkably correlated with a favorable prognosis and high immune infiltration in patients with TNBC.